2019
DOI: 10.5752/p.1984-6606.2019v19n52p101-117
|View full text |Cite
|
Sign up to set email alerts
|

O Cotidiano De Negócios Familiares Em Matozinhos/Mg

Abstract: Este trabalho tem como objetivo analisar a gestão no âmbito de cinco negócios familiares localizados no bairro Bom Jesus da cidade de Matozinhos, Minas Gerais. Tendo em vista o conceito de gestão ordinária, analisamos as estratégias e táticas cotidianas dos sujeitos por meio de suas ações. Para coleta de dados, foram realizadas onze entrevistas semiestruturadas e a análise dos resultados se deu por meio da análise do discurso na vertente francesa, sendo possível identificar dois percursos semânticos. O primeir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…It is essential mentioning that the studies by Certeau (2012) about daily life practices are not new in the Organizational Studies field. There are several studies addressing these strategic and tactical concepts, such as the ones conducted by Saraiva and Carrieri (2014), Honorato andSaraiva (2016), Cabaña andIchikawa (2017), Ribeiro et al (2019), Correia, Costanzi and Carrieri (2020), Saraiva and Ipiranga (2020), Magalhães and Saraiva (2021), Caleffi and Ichikawa (2021), Costa Júnior, Chagas and Oliveira (2022), among others.…”
Section: Ordinary Management Of/in Daily Life and The Territorializat...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential mentioning that the studies by Certeau (2012) about daily life practices are not new in the Organizational Studies field. There are several studies addressing these strategic and tactical concepts, such as the ones conducted by Saraiva and Carrieri (2014), Honorato andSaraiva (2016), Cabaña andIchikawa (2017), Ribeiro et al (2019), Correia, Costanzi and Carrieri (2020), Saraiva and Ipiranga (2020), Magalhães and Saraiva (2021), Caleffi and Ichikawa (2021), Costa Júnior, Chagas and Oliveira (2022), among others.…”
Section: Ordinary Management Of/in Daily Life and The Territorializat...mentioning
confidence: 99%
“…Strategy, within this association, refers to calculations, and it occupies a space of its own. Accordingly, strategy regards a practice that counts on a place typical of imposition (Cabana & Ichikawa, 2017;Correia;Costanzi & Carrieri, 2020).…”
Section: Ordinary Management Of/in Daily Life and The Territorializat...mentioning
confidence: 99%
“…They discovered managerialism models did not apply to the management of the previously mentioned cafeteria, observing that daily organizational life is rich in possibilities, creativity, and subversions to the hegemonic administrative culture. Correia and Carrieri (2019) researched five family businesses and observed contradictions regarding the discourses of separation of businesses and families. They also observed that the feeling of belonging in business is stimulated by family ties, making the activity productive and that these businesses often survive without formal employment ties, dependent on labour and family dynamics, subverting several rules and norms.…”
Section: Ordinary Managementmentioning
confidence: 99%
“…In this research, we start from an understanding of management that challenges the mainstream and considers the inclusion of marginalized subjects, their experiences and daily practices in the organizational environment (Gouvêa, Cabana & Ichikawa, 2018). To this end, we were inspired by the notion of "ordinary management" is already widely accepted in the field of organizational studies (Correia & Carrieri, 2019;Carrieri, 2018;Teixeira, Carrieri & Peixoto, 2015;Barros & Carrieri, 2015;Vale & Joaquim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Nesta pesquisa, partimos de uma compreensão de gestão que desafia o mainstream e considera a inclusão dos sujeitos marginalizados, suas vivências e práticas cotidianas no ambiente organizacional (Gouvêa, Cabana & Ichikawa, 2018). Para tanto, nos inspiramos na noção de "gestão ordinária", já bastante aceita no campo dos estudos organizacionais (Correia & Carrieri, 2019;Carrieri, 2018;Teixeira, Carrieri & Peixoto, 2015;Barros & Carrieri, 2015;Vale & Joaquim, 2017).…”
Section: Introductionunclassified